2016
DOI: 10.1016/j.celrep.2016.07.045
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Link between AMPK and Orexin Mediates the Effect of BMP8B on Energy Balance

Abstract: SummaryAMP-activated protein kinase (AMPK) in the ventromedial nucleus of the hypothalamus (VMH) and orexin (OX) in the lateral hypothalamic area (LHA) modulate brown adipose tissue (BAT) thermogenesis. However, whether these two molecular mechanisms act jointly or independently is unclear. Here, we show that the thermogenic effect of bone morphogenetic protein 8B (BMP8B) is mediated by the inhibition of AMPK in the VMH and the subsequent increase in OX signaling via the OX receptor 1 (OX1R). Accordingly, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
200
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(209 citation statements)
references
References 74 publications
8
200
0
1
Order By: Relevance
“…Mice were not under anaesthesia and no special preparation was needed before the measurements. Mice were placed in a holder of custom-defined size during the measurement (measuring time ranged between 0.5 and 3.2 min)323334.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mice were not under anaesthesia and no special preparation was needed before the measurements. Mice were placed in a holder of custom-defined size during the measurement (measuring time ranged between 0.5 and 3.2 min)323334.…”
Section: Methodsmentioning
confidence: 99%
“…This system is an open-circuit instrument that determines O 2 consumption, CO 2 production and respiratory quotient (vCO 2 /vO 2 )323334. Mice were acclimated for 1 week before starting the measurements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have identified higher levels of BMP8 expression as a molecular mechanism of estrogen-induced upregulation of metabolic activity in classic BAT of female mice [36]. Interestingly, recent studies demonstrated that thermogenic/browning effect of central BMP8b and AMPK activation in hypothalamus is restricted to female, showing estrogen dependency [34, 37, 38]. Further studies are needed to address whether the central regulation is involved in sex-dimorphic browning of gWAT.…”
Section: Discussionmentioning
confidence: 99%